Maka: distribution and circulation of an independent film (Altre Modernità, 2024)
The distribution and circulation of independent films are fundamental but often neglected aspects in film studies. This article presents a distribution experience followed by the author of the text himself: the case of the independent documentary Maka. Produced thanks to an academic grant and the collaboration with two Italian production companies, Maka was screened at numerous international festivals and received several awards. Distribution involved both traditional cinema circuits and independent digital platforms. The film has been screened in academic and associative contexts, in Italy and the United States, encouraging debates on social and cultural issues. The participation of the protagonist, the director, and the author in the screenings played a key role in the film's success, highlighting the importance of direct interaction with the audience for the dissemination of independent works.
Keywords: independent cinema; Maka; film distribution; academic filmmaking; migration cinema